Coached to death - Laurie, Victoria (Laurie, Victoria. Life Coach mysteries ;, 2019)
"Cat Cooper never imagined selling off her in-demand marketing firm would mean going from the pinnacle of success to a walking hot mess. Gouged from an unexpected divorce, Cat suddenly finds herself struggling through a new career as a business-savvy life coach for the hopelessly adrift in East Hampton and contending with Heather Holland--a spiteful neighbor who will do anything to bully her out of town. But her second act may very well continue behind bars when Heather's dead body turns up next to a shattered punchbowl...and Cat's pinned as the murderer. But given Heather's mean girl reputation, any one of the guests at her invite-only luncheon could have committed the crime before planting Cat's punchbowl next to the body. Determined not to trade designer duds for an unflattering prison jumpsuit, Cat sides with her best friend Gilley to scour chic boutiques and oceanfront mansions in search of the criminal who framed her. With a stoic detective looking to get her in cuffs, it's up to Cat to catch the real killer and land on her feet once again..."--